Integrated Application-Based Digital Learning Technology in Successful Learning Activities During the Pandemic - Mahsusi Mahsusi; Syihaabul Hudaa; Nuryani Nuryani; Ahmad Bahtiar; Makyun Subuki (Journal of Applied Engineering and Technological Science (JAETS), 2023)
This study aimed to look at madrasah's efforts in developing a learning system through "digital learning." This was done by examining the digital learning system implemented at MAN in terms of its advantages and disadvantages. The method used in this research was descriptive qualitative, with the data collection techniques employed were direct observation and interviews. Meanwhile, the research location is four MAN in Jakarta and Tangerang area, including. The four madrasahs that became the research locations were MAN Insan Cendekia Serpong (South Tangerang), MAN 1 Tangerang, MAN 4 Jakarta, and MAN 13 Jakarta. The researcher conducted interviews with school parties, namely teachers and principals. The results showed that three madrasahs have well-managed e-learning systems. In this case, they are MAN IC Serpong, MAN 1 Tangerang, and MAN 4 Jakarta. The e-learning system used by each madrasah is E-Learning Madrasah which can be accessed using the web and applications from Play Store. Meanwhile, MAN 13 Jakarta still needs to have its e-learning system and use standard features such as zoom, G-meet, etc. Basically. Madrasahs such as MAN IC Serpong, MAN 4 Jakarta, and MAN 1 Tangerang have registered to utilize the digital learning platform with all the features provided. Meanwhile, MAN 13 Jakarta has yet to register, so it cannot utilize the features contained in the digital learning platform. This research implies that madrasahs have innovated well in digital learning implementation so that learning during the pandemic can run well and smoothly. This research further contributes theoretically and practically to the world of education, especially for madrasas regarded as "second-class" schools. In general, this research contributes to the development of the world of digital learning by providing a valuable platform through the various features provided